Effect of D-tryptophan on hemolysin production in Vibrio parahaemolyticus. - Cherwonogrodzky, J W (1984)
Production of the Kanagawa hemolysin by a strain of Vibrio parahaemolyticus isolated from a gastroenteritis patient was found to correlate with the presence in cell lysates of two unidentified compounds, designated X and Y. The two compounds were present in cell lysates of the organism grown in peptone at the optimal pH for hemolysin synthesis but were not present when cell lysates were grown in peptone at a constant pH of 8.0. They were also absent in cells grown in synthetic medium at pH 6.2 without the addition of D-tryptophan, a condition under which hemolysin is not produced. Both X and Y were present intracellularly only from the time that D-tryptophan was added to synthetic medium, a known method of inducing hemolysin synthesis.